2017
DOI: 10.1080/13621718.2016.1274848
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural characterisation of double pulse resistance spot welded advanced high strength steel

Abstract: The effects of single and double pulse resistance spot welding on the microstructures of an advanced high strength automotive steel are presented in this work. The double pulse welding schemes partially remelt the primary weld nugget and anneal the area at the fusion boundary of the nugget. The effects of the annealing treatment on the segregation and the microstructure have been studied by electron probe microanalysis (EPMA) in combination with electron backscatter diffraction (EBSD). Results show that phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 23 publications
(41 reference statements)
1
35
1
Order By: Relevance
“…For thin sheets, the cooling mechanism of small welding nuggets is dominated by heat loss toward the cooled electrodes [29]. This can be visualized by the dendrites in the FZ, since they show a preferred orientation along the maximal thermal gradient [11]. In the inner FZ (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For thin sheets, the cooling mechanism of small welding nuggets is dominated by heat loss toward the cooled electrodes [29]. This can be visualized by the dendrites in the FZ, since they show a preferred orientation along the maximal thermal gradient [11]. In the inner FZ (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, several authors recommended a short cooling time between the pulses, leading to recrystallization of the outer FZ and consequently to the transformation of the cast-like structure. Eftekharimilani et al [11] illustrated that the shape of the prior austenite grains (PAGs) changes from an elongated to an equiaxed shape at the edge of the FZ. Furthermore, it is reported that segregations at the edge of the FZ are reduced after a second pulse, and therefore the risk of intergranular failure is reduced [12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Resistance spot welding has been widely used for AHSS to integrate into vehicle body-in-white structures, but some challenges remain to obtaining high weld qualities and mechanical joint properties. For example, segregation of alloying elements such as phosphorous and sulfur into the grain boundary during solidification inevitably deteriorated the toughness of the martensite, leading to low cross-tension strength [ 4 , 5 ]. Therefore, developing suitable welding techniques is essential for transportation industries, and developing new AHSS is essential for steel manufacturers.…”
Section: Introductionmentioning
confidence: 99%